Smart IOT Device for Pillbox Reminder and Monitor Using GSM - M.Prema, Dr.T.S.Jeyali laseetha (International Journal of Advanced Science and Technology, 2020)
Internet of things (IoT) is an environment which permits gadgets to be sensed and managed remotely at some point of existing community infrastructure, creating an opportunity for extra direct integration between the bodily international and computer-based gadget.  IoT has many packages collectively with smart homes, smart healthcare, smart metropolis, and many others. majorly IoT healthcare device is developed for patients, hospitals and healthcare facilities which might be regularly taking care of patients and additionally tests whether the affected person has taken the prescribed remedy or no longer. in present-day days, busy lifestyles have made many people forget to take the medicine at the right time (specifically for the elders). Not nice the elders are struggling but additionally the visually challenged humans are struggling masses to intake the drug treatments properly.  Fallacious of medication-taking for sufferers lead a ragging from moderate health issues up to lack of lifestyles. paper reviewing the era of home fitness care which can be presently used for reinforcing this example by method of reminding the schedule of drugs, far off track, sensing the temperature and coronary heartbeat of the sufferers and update new medicine statistics of sufferers, which may be performed by using prescriber through net.